Determining Future Strategies for Home & Living Online Business Using Scenario Planning Analysis (Case Study: Fluffy Fellas Studio) - Ayu Oktira Diyanti; Yudo Anggoro (Research Synergy Foundation, 2022)
Covid-19 pandemics are giving a huge impact and uncertainties. Both business owners and customers have to adapt in doing business activity, to face the challenge of shifting purchasing behavior to necessary spending through online shopping. Home and living products become one of the priorities that can be seen through the increasing supply and demand, because of the restriction of mobility, that makes people more aware about their home decoration. Fluffy Fellas Studio is one of the home and living businesses which started in a pandemic and within a year, some of the products managed to become the top 3 best sellers in one of the marketplace in Indonesia, with increasing number of visitors and sales every month, but the retention and conversion rate are decreasing every month. Since the future challenges are still unpredictable, scenario planning framework is used to define four alternative solutions. The key focal issue of the research is what plausible scenarios and future strategies are suitable for Fluffy Fellas in 2 years. The critical uncertainties of Fluffy Fellas are Covid-19 pandemics and industry dynamics, which resulted in four scenarios assigned with their own narratives, implications, options, and early warning signals which should be analyzed carefully to determine which scenario to be implemented. To better prepare for all the scenarios, Fluffy Fellas should prioritize the improvement in supply chain, research and development, and social media planning. Keywords: Covid-19; Scenario Planning; Home & Living